Status of Road Ecology Research in Africa: Do We Understand the Impacts of Roads, and How to Successfully Mitigate Them? - Collinson, Wendy; Davies-Mostert, Harriet; Roxburgh, Lizanne; van der Ree, Rodney (Frontiers in Ecology and Evolution, 2019)
Across Africa, transport infrastructure, including roads, is being built in over 30 planned development corridors that are likely to have major impacts on remaining natural habitats and associated biodiversity. Linked to this is the projected increase in human population size, which is predicted to grow by 1.3 billion people by 2050. Road ecology is the study of the ecological effects of roads and traffic but is perceived to be under-researched in Africa. In this context, we undertook a systematic review of road ecology research in Africa to understand the geographic and taxonomic scope of work undertaken to date, as well as recommendations for reducing the impacts of roads. We discovered 210 road ecology publications from Africa (1954 and 2016), with most publications from the more affluent and politically stable regions (e.g., southern and East Africa). We found more publications than expected, with relevant research concealed within studies whose primary focus was on other topics. Most publications 1) focused on single species, and in particular on mammals (chimpanzees and forest elephants); 2) were from southern Africa; and 3) were conducted in the grassland and savannah biome and the tropical and subtropical forest biome. Most publications examined the direct impacts of roads, in particular wildlife-vehicle collisions. Only one-third of the publications provided some form of recommendation for intervention to reduce or mitigate the impacts of roads, based on evidence from the publication. Most recommended interventions related to ecosystem or natural process recreation, as well as site and area stewardship. Gaps and future directions for research include rigorous testing of measures to mitigate the impacts of roads, inclusion of traffic monitoring in studies, understanding the impacts of upgrading roads, and exploring livelihood, economic and moral incentives and education and training as potential interventions for reducing the impacts of roads. Our review has highlighted the need for accelerating the study of the impacts of roads on natural habitats and biodiversity, in light of planned large-scale infrastructure development, and especially the study of appropriate mitigation measures that can be rigorously assessed and implemented before and during construction and upgrading of roads in Africa.